Producción, comercialización y rentabilidad del etanol y su relación con la economía del cantón La Maná, provincia de Cotopaxi, año 2011 - Miranda Guaman, Diana Carolina (2013)
Cotopaxi Province has more than 100 years in the production of sugar cane and its derivatives such as juice, ethanol and sugar cane, the Canton La Maná counted by the National Agricultural Census IV with 315 Agricultural Production Units (WCU) in an area of 741 ha, where the prevailing Cuban varieties - Creole (POJ-2878) and Cunchibina (Ragnar). The study aims to determine the production, marketing and profitability of ethanol and its relationship to the economy of the county for which surveys at five producers and 132 consumers. The results revealed that 60% of producers lead in this activity more than 15 years, own their own land and 40% have 2 ha for the production of sugar cane for ethanol production which use neither technology nor fertilizers, to produce 40 liters of ethanol need 200 rods....